Biological and economic optima in a tropical grazing ecosystem in Australia - Izac, A.M.N.; Anaman, K.A.; Jones, R. (Elsevier, 1990)
Our aim in this study was to identify the economically optimal level of use of resources for a grazing system in tropical Australia and to compare it with the biological optimum. Grazing management trials were conducted in the Ord River irrigation area of north-western Australia. Biologists at the Commonwealth Scientific and Industrial Research Organization provided the biological data. The liveweight gains of Kimberley shorthorn steers were recorded, after a 1-year fattening period, for different grazing management strategies. Five different stocking rates were used on irrigated pangola grass (Digitaria decumbens) fertilized with nitrogen at five different rates. All other were applied at fixed, non-limiting levels.The results of the trials were modelled by a liveweight gain production function. This production function was used in an income simulation model to identify economically optimal (profit maximizing) stocking rates. This was done in two stages. First, a base analysis was undertaken on the basis o the economic conditions prevailing in September 1987. Second, sensitivity analysis was applied to the results of the base analysis. The parameters varied were the rate of interest, store cattle prices, finished cattle prices, transport costs and the length of the planning horizon. The biological optimum, when defined as maximum liveweight gain ha−1, corresponds to a much higher intensity of use of resources than the economic optimum, and yields substantially lower profits or higher losses. These discrepancies increase when economic conditions worsen, or when the planning horizon of graziers is decreased from 50 to 10 years. Therefore, the adoption of the biological optimum cannot result in an econonomically stable grazing system in the medium to long term, when it is highly likely that economic parameters will fluctuate. The economic stability of the system is increased, but is still quite weak, if the economically optimal input combination is utilized. It was not possible to determine whether this economic optimum would result in long-term ecological stability because the relevant data were not collected during the trials. The relevance of management recommendations made to graziers and land administrators would be increased if these recommendations were based on an analysis of both the economic and the ecological stability of grazing systems over the medium to long term. We show in the last part of this study how this could be accomplished.